1990
DOI: 10.1080/00380768.1990.10416797
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic matter application on methane emission from some Japanese paddy fields

Abstract: Emission rates of CH4 from four Japanese paddy fields were measured throughout the cultivation period in 1988 by using the closed chamber method. Large seasonal variations of the CH4 flux were observed. The emission was closely related to the decrease of the redox potential (Eh) in paddy soils. Drainage and supplementary application of mineral fertilizer substantially reduced the CH4 emission. Emission rates of CH4 differed markedly with the soil types. The highest rate was observed in a paddy field consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
275
7
11

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 569 publications
(326 citation statements)
references
References 28 publications
28
275
7
11
Order By: Relevance
“…Minoda and Kimura (1994) Methane emission rates to the atmosphere from the pot without percolation were significantly lower than those from the pot with percolation. These results are not in agreement with the previous studies (Yagi et al 1990;Murase et al 1993). It is suggested that percolation accelerated methane production in this experiment.…”
Section: Resultscontrasting
confidence: 56%
“…Minoda and Kimura (1994) Methane emission rates to the atmosphere from the pot without percolation were significantly lower than those from the pot with percolation. These results are not in agreement with the previous studies (Yagi et al 1990;Murase et al 1993). It is suggested that percolation accelerated methane production in this experiment.…”
Section: Resultscontrasting
confidence: 56%
“…Previous studies show that the emission of CH 4 is closely related to temperature. There is little CH 4 emission from rice paddies, rivers and lakes when the temperature is lower than 15°C, whereas much more CH 4 is emitted at temperatures of 35°C than in 25°C [33][34][35][36][37][38][39]. Waste decomposition is another important biological source of methane.…”
Section: Seasonal Cycle Of Ch 4 Over Chinamentioning
confidence: 99%
“…Rice straw and remaining plant residue, such as rice stubble and roots, are ploughed into the soil at the beginning of the growing season to act as organic fertilizers. Such additions often result in an increase in methane emission rates from the fields (Yagi & Minami, 1990;Watanabe et al, 1995;Wassman et al, 2000a). In a previous study, we reported the enumeration and isolation of anaerobic fermentative bacteria from rice-plant residue ploughed into the soil of a Japanese rice field (Akasaka et al, 2003).…”
Section: Introductionmentioning
confidence: 99%